SEASONAL THERMAL ENERGY STORAGE - THE HYDROCK CONCEPT - Hellstrom G.; Larson S.A. (My University, 2001)
A method for seasonal storage of heat or cold in the bedrock (the HYDROCK concept) is presented and its thermal performance discussed. It involves the use of a fractured bedrock at shallow depths (ca. 50-250 m), where existing fractures are stimulated or new fractures artificially created and used as flow-paths for a heat/cold carrier (usually water). The fracture surfaces are used as heat exchangers and the bedrock is loaded and unloaded to suit the energy needs. Propants are injected into the fractures to keep them open and reduce the energy needed for pumping water through the system. Field tests confirm that stacked parallel fractures can be produced by hydraulic fracturing. The thermal performance of the store is modelled and compared with a ducted ground heat store. It is shown that the HYDROCK store may yield 10-20% more energy during extraction than a ducted ground heat store for similar amounts of injected energy. This indicates that the HYDROCK concept is competitive as a seasonal energy store and may be of particular importance as an alternative energy source where existing methods cannot be economically justified.
Keywords: ENERGY STORE; SEASONAL; THERMAL; HYDRAULIC FRACTURING; HYDROCK